Analisis Praktik Giveaway Dalam Perspektif Ekonomi Syariah di Akun Instagram Arifah.id - Temmy Zamilah; Rina Nurhayati; Eka Ahadiyat Suryana (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2022)
Every company must have a promotional media, one form of promotion that is mostly done by online shop business actors is to hold a giveaway. The purpose of this study is to find out the practice of giveaway on the Arifah.id Instagram account and to find out the giveaway practice on the Arifah.id Instagram account in the perspective of Islamic Economics. This research method uses qualitative research methods. And the research approach used is a case study approach. The results of this study, First, the holding of the giveaway on the Arifah.id Instagram account begins with the owner determining the requirements for participants who take part in the giveaway, after that the requirements and prizes are submitted in the Arifah.id Instagram account post, then participants follow the terms and conditions according to what has been submitted. in the Instagram post, then the owner determines the winner manually. After the winner is determined, the owner announces the giveaway winner on Instagram story by marking the winner's Instagram account, then the winner confirms personal data such as Full Name, Complete Address, No. Mobile phones, as well as prizes that the winners want from Arifah.id products. After receiving confirmation from the winner, the owner prepares the prize and sends the prize via J&T or JNE expedition, without any requirements for the winner to send the prize. Second, the practice of giveaway in the perspective of sharia economics is included in the ju'alah contract. The giveaway practice on Arifah.id's Instagram account is in accordance with the Fatwa of the National Sharia Council-Indonesian Ulema Council Number 62/DSN-MUI/XII/2007. This can be shown by fulfilling the pillars and conditions in the ju'alah contract, starting from Ja'il (the party holding the contest), Maj'ul Lah (the party doing the work of the competition and who is entitled to receive wages (ju'lu)), ' Amal (works that are contested), Ju'lu (promised wages), and Sighat (statements from the ja'il to maj'ul lah). And this research is also strengthened by Islamic Economics Experts that the practice of this giveaway is in accordance with sharia terms and conditions, which means it is permissible in Islam, because basically all forms of muamalah are allowed unless there is an argument that forbids it.